Impact of Renal Impairment on the Pharmacodynamic and Pharmacokinetic Profiles of Epaminurad, a Novel Uric Acid Transporter 1 Inhibitor - Seo Yeong Park; Jun Gi Hwang; Sung Kweon Cho; Min Kyu Park (Clinical and Translational Science)
ABSTRACT Epaminurad, a novel uricosuric agent, exhibits potent inhibitory activity against the human uric acid transporter. This study aimed to investigate the effects of renal function and food intake on the pharmacokinetic, pharmacodynamic, and safety characteristics of 9 mg epaminurad. This study was designed as a phase 1, partially randomized, open‐label, oral administration, partial crossover trial. Participants were assigned to three groups based on renal function: normal (Group 1), moderate renal impairment classified as Stage 3a (Group 2) and Stage 3b (Group 3). Each group aimed to enroll 6–10 participants. Blood and urine samples were collected to evaluate the pharmacokinetics and pharmacodynamics of epaminurad. Safety assessments were also conducted throughout the study. A total of 27 participants completed the study, including 12 with normal renal function (Group 1) and 9 and 6 participants with moderate renal impairment (Groups 2 and 3), respectively. When a single 9 mg dose of epaminurad was administered under fasted conditions, the pharmacokinetic, pharmacodynamic, and safety profiles did not show clear differences among the renal function groups. Furthermore, no notable differences were observed in these profiles between the fasted and fed states. Patients with moderate renal impairment can receive (eGFR of 30–59 mL/min/1.73 m2) 9 mg epaminurad without dose adjustment, and the drug may be administered regardless of food intake.